EASIX-1year and late mortality after allogeneic stem cell transplantation - Kordelas, Lambros; Terzer, Tobias; Gooley, Ted; Davis, Chris; Sandmaier, Brenda M.; Sorror, Mohamed; Penack, Olaf; Schaeper, Nigel D. E.; Blau, Igor-Wolfgang; Beelen, Dietrich W.; Radujković, Aleksandar; Dreger, Peter; et al. (Blood advances, 2023)
Abstract - Patients with hematological malignancies who survive the first year after allogeneic stem cell transplantation (allo-SCT) without relapse have a substantial risk of nonrelapse mortality (NRM) and missing predictive markers. The Endothelial Activation and Stress Index (EASIX) predicts endothelial complications and NRM early after allo-SCT. We hypothesized that EASIX assessed 1 year after allo-SCT in survivors who were disease free may predict late NRM. Survivors who were relapse-free at 1 year after allo-SCT were retrospectively studied in 2 independent cohorts (training cohort, n = 610; merged validation cohort, n = 852). EASIX determined 1 year after allo-SCT correlated with the overall survival (OS), NRM, and relapse. Serum endothelial and inflammatory markers were measured in the training cohort and correlated with EASIX-1year, which predicted OS and NRM but not relapse risk in both the training and validation cohorts in univariable and multivariable Cox regression analyses. Brier score and c-index analyses validated the univariable EASIX effects. There was no significant interaction between EASIX-1year and incidence of chronic graft-versus-host disease (GVHD) on OS. EASIX-1year predicted the outcome irrespective of preexisting comorbidities. Principal causes of NRM in both training and validation cohorts were infections with and without GVHD as well as cardiovascular complications. EASIX-1year correlated with sCD141 and interleukin-18 but not with C-reactive protein, suppressor of tumorigenicity-2, angiopoietin-2, CXCL9, or CXCL8. To our knowledge, EASIX-1year is the first validated predictor of late overall and NRM. Patients who are high risk as defined by EASIX-1year might be considered for intensified surveillance and prophylactic measures.
Gesehen am 08.01.2024